Modified Goff Symptom Index : Simple triage tool for ovarian malignancy - Jyothi Shetty; Priyadarshini P.; Deeksha Pandey; Manjunath A. P. (Sultan Qaboos University Medical Journal, 2015)
Objectives: Ovarian cancer often goes undiagnosed or misdiagnosed in the early stages. The present study aimed to validate a modified version of the Goff Symptom Index (GSI) in an Indian population. Methods: This prospective case-control study was conducted between July 2010 and June 2012 in a university hospital in Manipal, Karnataka, India. A total of 305 inpatients admitted for ovarian pathology investigations and outpatients undergoing routine gynaecological check-ups were included in the study. The modified GSI (MGSI) was used to investigate the presence, severity, frequency and duration of 10 ovarian cancer symptoms on a scale of 1–5. Four additional symptoms were included with those of the original GSI (two symptoms from a previous MGSI and two new symptoms). Patients were regarded as positive for ovarian cancer if symptoms occurred >12 times per month and time since onset was <1 year. Histopathology confirmed the diagnosis of ovarian tumours. Results: A total of 13 patients were excluded. The final sample (n = 292) was divided into a test group (n = 74) and a control group (n = 218) based on histopathology. Within the controls, 144 women were found to have benign tumours. The MGSI was positive in 71.6% of the test group as opposed to only 11.5% of the control group. The addition of two symptoms (loss of appetite and weight) to the GSI increased the test’s sensitivity from 71.6% to 77% without compromising specificity (88.5%). Conclusion: Based on these findings, the addition of two new symptoms (loss of appetite and weight) to the GSI is proposed in order to increase the test’s sensitivity. However, the addition of urinary symptoms to the GSI requires further validation.